IMPLEMENTASI MEDIA RODA SUKU KATA UNTUK MENINGKATKAN MEMBACA PEMULA PADA PESERTA DIDIK DI SEKOLAH DASAR (SD) - Nofia Handayani Dalimunthe; Akmal Walad Ahkas; Aufa Aufa (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The problem in this research is the implementation of syllable wheel media to improve beginner reading among students at Elementary School (SD). How to implement the implementation of the syllable wheel media to improve the reading of beginner students. This research aims to find out how the syllable wheel is implemented to improve students' beginner reading and to find out the supporting and inhibiting factors in the use of syllable wheel media. This type of research uses descriptive qualitative field research. The subjects of this research were teachers and students of Madrasah Ibtidaiyah Andalusia. There are 3 data collection techniques used in this research, namely, interviews, observation and documentation. Based on research conducted, the implementation of the syllabic wheel media has an important role for students in improving beginner reading at Madrasah Ibtidaiyyah Andalusia.